Winds of Change : The Case for New Digital Currency. (International Monetary Fund, 2019)
This paper explores impact of new digital currency on Singapore. A new wind of digitization is blowing. Even cryptocurrencies such as Bitcoin, Ethereum, and Ripple are vying for a spot in the cashless world, constantly reinventing themselves in the hope of offering more stable value, and quicker, cheaper settlement. Providers of e-money argue that they are less risky than banks, because they do not lend money. Instead, they hold client funds in custodian accounts, and simply settle payments within their networks. If most people adopt digital forms of money, the infrastructure for cash would degrade, leaving those in the periphery behind. The second benefit of digital currency relates to security and consumer protection. Digital currency offers great promise through its ability to reach people and businesses in remote and marginalized regions. A digital currency could boost competition by offering a low-cost and efficient alternative means of payment.